Silver-decorated gel-shell nanobeads: physicochemical characterization and evaluation of antibacterial properties - Bartel, Marta; Markowska, Katarzyna; Strawski, Marcin; Wolska, Krystyna; Mazur, Maciej (Beilstein Journal of Nanotechnology, 2020)
We report on the synthesis of composite nanobeads with antibacterial properties. The particles consist of polystyrene cores that are surrounded by sulfonic gel shells with embedded silver nanoparticles. The nanocomposite beads are prepared by sulfonation of polystyrene particles followed by accumulation of silver ions in the shell layer and subsequent reduction with sodium borohydride. The resulting material has been characterized by electron microscopy, vibrational and X-ray photoelectron spectroscopy and several other experimental techniques. It was shown that sodium borohydride reduces silver ions embedded in the gel layer producing silver nanoparticles but also transforms a fraction of sulfonic groups in the polymer to moieties with sulfur in a lower oxidation state, likely thiols. It is hypothesized that the generated thiol groups are anchoring the nanoparticles in the gel shell of the nanobeads stabilizing the whole structure. The silver-decorated nanobeads appear to be a promising material with considerable antimicrobial activity and were tested against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Staphylococcus epidermidis. The determined minimum inhibitory (MIC) and minimum biofilm inhibitory (MBIC) concentrations are comparable to those of non-incorporated silver nanoparticles.
Keywords: Escherichia coli; gel-shell particles; minimum biofilm inhibitory concentration (MBIC); minimum inhibitory concentration (MIC); nanocomposites; Pseudomonas aeruginosa; silver nanoparticles; Staphylococcus sp